Tros, Tevodas, and Haircuts: Ritual, Music, and Performance in Khmer Wedding Ceremonies - McKinley, Kathy (Canadian University Music Review / Revue de musique des universités canadiennes, 1999)
This paper explores the importance of musical performance, its purpose and significance within Cambodian wedding ceremonies. While social and economic conditions of the early 1990s have contributed to the affordability of live wedding music in Phnom Penh, this paper suggests that the primary reason for the maintenance of live traditional wedding music is its role in enhancing the ritual and social efficacy of the ceremony, achieved through inspired and connected performances by singer-musicians as social-ritual actors.